Cloning and Characterization of a 5-Enolpyruvyl Shikimate 3-Phosphate Synthase (EPSPS) Gene from Korean Lawn Grass (Zoysia japonica) - Lee, H.J., Advanced Radiation Technology Institute, Korea Atomic Energy Research Institute, Jeongeup, Republic of Korea; Lee, G.J., Mokpo National University, Muan, Republic of Korea; Kim, D.S., Advanced Radiation Technology Institute, Korea Atomic Energy Research Institute, Jeongeup, Republic of Korea; Kim, J.B., Advanced Radiation Technology Institute, Korea Atomic Energy Research Institute, Jeongeup, Republic of Korea; Ku, J.H., Chungnam National University, Daejeon, Republic of Korea; Kang, S.Y., Advanced Radiation Technology Institute, Korea Atomic Energy Research Institute, Jeongeup, Republic of Korea (Weon'ye gwahag gi'sulji, 2010)
This study is the first comprehensive report on the molecular cloning, structural characterization, sequence comparison between wild and mutant types, copy number in the genome, expression features and activities of a gene encoding 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) in Korean lawn grass (Zoysia japonica). The full length cDNA of the EPSPS from Korean lawn grass (zjEPSPS) obtained from a 3' and 5' RACE method was 1540 bp, containing a 1176 bp ORF, a 144 bp leader sequence (5' UTR) and a 220 bp 3' UTR, which was eventually decoded 391 amino acid residues with a molecular mass of 41.74 kDa. The Southern blot detection of the zjEPSPS showed that the gene exists as a single copy in the Korean lawn grass genome. Sequence comparison of the zjEPSPS gene demonstrated that the glyphosate-tolerant mutant (GT) having a Pro-53 to Ser substitution in the gene seems to have a preferred binding activity of the enzyme to phosphoenol pyruvate(PEP) over glyphosate, which allows the continuous synthesis of aromatic amino acids in the shikimate pathway. From the Northern blotting analysis, the zjEPSPS was found to be highly expressed, with continuous increase until 36 hours after 0.5% glyphosate treatment in both wild and mutant samples, but 1.5-fold higher EPSP synthase activity was observed in the tolerant mutant when exposed to the glyphosate treatment. The molecular information of the zjEPSPS gene obtained from this study needs to be further dissected to be more effectively applied to the development of gene-specific DNA markers and zoysiagrass cultivars; nevertheless, the glyphosate-tolerant mutant having the featured zjEPSPS gene can be provided to turfgrass managers for weed problems with timely adoptable management options.